The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1413-81232012000800021
|View full text |Cite
|
Sign up to set email alerts
|

A configuração do trabalho da enfermeira na atenção ao idoso na Estratégia de Saúde da Família

Abstract: Este artigo teve como objetivo descrever a configuração do trabalho da enfermeira com o idoso na Estratégia de Saúde da Família (ESF), destacando as ações nas quais se concentram a sua atuação. Caracterizou-se como um estudo exploratório-descritivo de natureza qualitativa que teve como informantes enfermeiras que atuam na ESF do município de Florianópolis/SC. As informações foram coletadas por meio da entrevista narrativa e os resultados foram submetidos à técnica de Análise de Conteúdo, originando três catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 3 publications
1
6
0
8
Order By: Relevance
“…The situation described seems to corroborate the results of another study, 8 in which the nurse, when performing the nursing consultation (NC) with the elderly, focused care on the complaints they presented, with a curative proposal, aiming at the disease and rather than at the human being.…”
Section: ] There Is a Lot Of Demand For This Population The Care Atsupporting
confidence: 79%
“…The situation described seems to corroborate the results of another study, 8 in which the nurse, when performing the nursing consultation (NC) with the elderly, focused care on the complaints they presented, with a curative proposal, aiming at the disease and rather than at the human being.…”
Section: ] There Is a Lot Of Demand For This Population The Care Atsupporting
confidence: 79%
“…No entanto, além de ações de gerência e planejamento, o enfermeiro desenvolve ações de cuidado direto e práticas educativas, que podem ser entendidas como estratégia de cuidado ampliado e integral na Estratégia Saúde da Família (ESF) (53) . O enfermeiro pode desenvolver na unidade de saúde atividades como os procedimentos específicos de sua categoria profissional na assistência, dentre eles: consulta de enfermagem, visita domiciliar, grupos, atividades de apoio e supervisão ao trabalho do agente comunitário de saúde (ACS) e do técnico ou auxiliar de enfermagem; soma-se a gerência da unidade de saúde (54) .…”
Section: Discussionunclassified
“…Já pesquisa realizada entre enfermeiros observou que as ações na ESF estão fundamentadas no modelo biomédico, não atendendo às recomendações nacionais dos documentos oficiais que regulamentam a sua implantação e funcionamento (54) .…”
Section: Discussionunclassified
“…25 The analyzed articles point out that the elderly attended in the Hiperdia program, included in the Nurses' agenda for consultation, focused on monitoring diseases included in the program (hypertension and diabetes mellitus), which compromised the comprehensive care to the elderly by the nurse. 26 In addition, another article mentions the fact that hypertensive patients have reported that the NC is often reduced to following the prescription. 27 Moreover, there are good experiences within the vertical mold of health care.…”
Section: Vertical and "Medicalized" Attentionmentioning
confidence: 99%